2000
DOI: 10.1103/physrevd.61.113005
|View full text |Cite
|
Sign up to set email alerts
|

Neutrino parameters, Abelian flavor symmetries, and charged lepton flavor violation

Abstract: Neutrino masses and mixings have important implications for models of fermion masses, and, most directly, for the charged lepton sector. We consider supersymmetric Abelian flavor models, where neutrino mass parameters are related to those of charged leptons and sleptons. We show that processes such as τ → µγ, µ → eγ and µ − e conversion provide interesting probes. In particular, some existing models are excluded by current bounds, while many others predict rates within reach of proposed near future experiments… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(34 citation statements)
references
References 29 publications
0
34
0
Order By: Relevance
“…SUSY can accommodate the observed flavor mixing [8,9,10] and thus, the LFV processes (15), (16) and (17) would arise in these models. A study conducted at the LHC showed that an upper bound of 0.6 × 10 −6 on the τ ± → µ ± γ branching ratio can be achieved with an integrated luminosity of 30 fb −1 while theoretical estimates are at the level of 10 −9 or less [10,32].…”
Section: Collider Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…SUSY can accommodate the observed flavor mixing [8,9,10] and thus, the LFV processes (15), (16) and (17) would arise in these models. A study conducted at the LHC showed that an upper bound of 0.6 × 10 −6 on the τ ± → µ ± γ branching ratio can be achieved with an integrated luminosity of 30 fb −1 while theoretical estimates are at the level of 10 −9 or less [10,32].…”
Section: Collider Experimentsmentioning
confidence: 99%
“…However LFV effects can be induced by * Electronic address: ketevi@bnl.gov † Electronic address: deandrea@ipnl.in2p3.fr ‡ Electronic address: delsart@ipnl.in2p3.fr radiative corrections [6]. Large LFV effects can arise in supersymmetric models (SUSY) with a right-handed Majorana neutrino [7,8,9,10] and in SUSY with R-parity violation [11].…”
mentioning
confidence: 99%
“…For instance, the LFV tau decays, such as τ → µγ, τ → eγ, τ → 3µ and τ → 3e, have been studied in a model independent way in Ref. [12], in the SM with extended right-handed and left-handed neutrino sectors [13], in supersymmetric 2 models [14], in the two Higgs doublets model type III [15] and in Zee model [16].…”
Section: Introductionmentioning
confidence: 99%
“…While this paper was in the final stages of preparation, we received the paper by Feng, Nir and Shadmi in [9], which makes points similar to ours, in a complimentary way.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Neutrino oscillations involve violations of the individual lepton numbers L e,µ,τ , raising the prospect that there might also exist observable processes that violate charged-lepton number conservation [4,5], such as µ → eγ, 3e and τ → µγ, 3µ/e, and µ → e conversion on heavy nuclei [5,6,7,8,9,10]. We recall briefly the present experimental upper limits on the most interesting of these decays for our subsequent discussion:…”
Section: Introductionmentioning
confidence: 99%